2017
DOI: 10.1175/jtech-d-16-0238.1
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Tidal Open Boundary Conditions of the M2 Constituent in the Bohai and Yellow Seas

Abstract: Open boundary conditions (OBCs) of the M2 tidal constituent in the Bohai and Yellow Seas (BYS) were inverted successfully through assimilation of TOPEX/Poseidon (T/P) altimeter data. An improved independent points (IPs) scheme was employed in the inversion. Under the assumption that the OBC was spatially varying, values at a set of IPs along the open boundary were inverted using the adjoint method and those at other points were calculated by the spline interpolation. The OBC inverted with the improved scheme w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…But different from NS_TIDE, equation is solved with the IP scheme (Guo et al, ; Lu & Zhang, ; Pan et al, ; Zhang et al, ). The basic idea of the IP scheme is very simple: see Figure for example.…”
Section: Performance Of Different Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…But different from NS_TIDE, equation is solved with the IP scheme (Guo et al, ; Lu & Zhang, ; Pan et al, ; Zhang et al, ). The basic idea of the IP scheme is very simple: see Figure for example.…”
Section: Performance Of Different Methodsmentioning
confidence: 99%
“…The cubic spline interpolation is widely implemented due to its stable, convergent, and smooth characteristics (Huang et al, ; Malik et al, ; Pan et al, ). Therefore, it is adopted in the present scheme.…”
Section: Performance Of Different Methodsmentioning
confidence: 99%
“…On the contrary, the surface spline interpolation (SSI) has a better performance in producing a smooth curved surface and it has a wide range of applications (Guo et al, 2017;Pan et al, 2017). Perrin et al (1987) applied the SSI to mapping scalp potentials and the comparison with linear interpolation showed that result of the spline method is smoother and gives more precisely local extrema.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Fan and Lv [11], SeaWiFS chlorophyll-a data were assimilated into a NPZD (Nutrient-PhytoplanktonZooplankton-Detritus) model by the adjoint method; Pan et 2 Advances in Mathematical Physics al. [12] studied the open boundary condition of the M 2 tidal constituent using the adjoint method of data assimilation with spline interpolation; Zhang et al [13] applied this method to study the similarities and the differences between the Ekman (linear) and the Quadratic (nonlinear) bottom friction parameters of a two-dimensional tidal model; and many other researches (Yu and O'Brien [14], Lawson et al [15], Zhao et al [16], Zhao and Lu [17], and Qi et al [18]) have also proven the validity and rationality of the adjoint method.…”
Section: Introductionmentioning
confidence: 99%